Influence of management and lactation order in the serum concentrations of proteins, metabolites, minerals, and enzymes of Bonsmara breed cows - Barbosa, Fernando Cristino; Oliveira, Wilson Junior [UNESP]; Faria, João Gabriel Knychala; Gonçalves, Felipe Cesar; Guimarães, Ednaldo Carvalho; Mundim, Antonio Vicente (Universidade Federal de Goiás, 2022)
This study aimed to evaluate the influence of gestation and lactation order on serum concentrations of proteins, metabolites, minerals, and enzymes in first-, second-, and third-lactation order Bonsmara cows. The Bonsmara breed, originated in South Africa, stands out for its tolerance to heat and productive characteristics, such as meat quality, high fertility, sexual precocity, ease of calving, and good maternal ability. These characteristics make the breed a genetic alternative for crossbreeding with zebu breeds. Blood samples were collected from 34, 29, and 30 first-, second-, and third-lactation order cows, respectively, totaling 93 cows. The samples were processed in an automatic multichannel analyzer using Labtest Diagnóstica® kits. The Kruskal-Wallis test was chosen to compare the values between lactation orders. The Mann-Whitney test was used to compare pregnant and non-pregnant cows within lactation orders. Among the analyzed constituents, the lactation order significantly influenced only the serum albumin concentration (ALB) (p<0.0001). Gestation significantly influenced the A:G ratio (p=0.034) in third-lactation cows, and cholesterol (Chol) (p=0.004), triglycerides (TRI) (p<0.0001), inorganic phosphorus (iP) (p=0.033), iron (Fe) (p=0.001), aspartate aminotransferase (AST) (p=0.018), and alkaline phosphatase (ALP) (p=0.039) in second-lactation cows and the general group. Creatinine (Crea) (p<0.0001) was influenced only in the general group. Therefore, gestation and lactation order significantly influenced the concentration of several biochemical serum constituents in Bonsmara cows, especially second-lactation order cows.
Keywords: Beef cattle; Production phases; Serum biochemistry; Metabolic profile